2018
DOI: 10.2528/pierl18092605
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Location of Nonlinear Scatterers Using Dort Applied With Pulse Inversion

Abstract: In this paper, an experimental demonstration employing the decomposition of the timereversal operator (known as DORT) in combination with pulse inversion is reported, allowing one to detect and selectively focus on nonlinear targets. DORT is a technique based on a multistatic configuration that separates the detected targets by means of eigendecomposition of the time reversal operator allowing for selective transmission of waves towards a target of interest. Pulse inversion is a technique that enhances harmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…11 The initial motivation for obtaining added gain in the bow-tie antenna described here is due to its role as a scattering target in our active investigation of multistatic detection for smart far-field wireless power transmission. [12][13][14] This work employs a multistatic detection technique involving time-reversal and pulse inversion to permit nonlinear targets, formed by connecting a passive rectifier to an antenna (to form a rectenna), to be located and distinguished. Because this technique is based on detection of harmonic responses, the antenna must have an ultrawide bandwidth and enhanced gain will result in increased backscattered energy.…”
Section: Introductionmentioning
confidence: 99%
“…11 The initial motivation for obtaining added gain in the bow-tie antenna described here is due to its role as a scattering target in our active investigation of multistatic detection for smart far-field wireless power transmission. [12][13][14] This work employs a multistatic detection technique involving time-reversal and pulse inversion to permit nonlinear targets, formed by connecting a passive rectifier to an antenna (to form a rectenna), to be located and distinguished. Because this technique is based on detection of harmonic responses, the antenna must have an ultrawide bandwidth and enhanced gain will result in increased backscattered energy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by feeding the array using the eigenvectors associated with a given eigenvalue, it is possible to selectively transmit waves onto a detected target of interest, either physically for focusing electromagnetic energy at the scatterer or virtually for imaging purposes. For this reason, DORT has been studied for various applications [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent demonstration has shown that DORT can also be applied to detection of passive nonlinear scatterers in the presence of linear scatterers [10,11]. Nonlinear scatterers refer to electronic devices containing semiconductor junctions which can generate harmonic responses upon excitation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations